The Potential Role of Korean Mistletoe Extract as an Anti-Inflammatory Supplementation - Soo-Min Ha; Ji-Hyeon Kim; Jong-Won Kim; Do-Yeon Kim; Min-Seong Ha (Journal of Immunology Research)
Korean mistletoe has anti-inflammatory and antioxidant functions and may be a useful training supplement. We investigated the effect of Korean mistletoe extract (KME) on inflammatory markers after high-intensity exercise by 20 university male rowers (KME group vs. CON group) consuming 110 mL KME/dose (2 times a day over 8 weeks). Blood samples were collected for measurement of serum cytokine levels at baseline, immediately after exercise, and following 30 minutes of recovery. Interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), and C-reactive protein (CRP) were used as markers for inflammation. After supplementation, IL-6 and TNF-α levels were significantly lowered in the KME group than in the CON group at baseline, immediately after exercise, and following 30 minutes of recovery. KME can reduce high-strength exercise-induced increases in the levels of serum inflammatory cytokines in active individuals and improve anti-inflammatory functions.